Land health surveillance and response: a framework for evidence-informed land management - Shepherd, Keith D.; Shepherd, G.; Walsh, Markus G. (Elsevier, 2015)
Degradation of land health – the capacity of land, relative to its potential, to sustain delivery of ecosystem services – is recognized as a major global problem in general terms, but remains poorly quantified, resulting in a lack of specific evidence to focus action. Land health surveillance and response is designed to overcome limitations of current assessment approaches. It is modelled on science principles and approaches used in surveillance in the public health sector, which has a long history of evidence-informed policy and practice.